2018
DOI: 10.1021/acscatal.7b04271
|View full text |Cite
|
Sign up to set email alerts
|

Calcium(II)-Catalyzed Intra- and Intermolecular Hydroamidation of Unactivated Alkenes in Hexafluoroisopropanol

Abstract: A combination of a calcium(II) triflimide salt and hexafluoroisopropanol (HFIP) was found to be a highly efficient promoter system for the intra-and intermolecular hydroamidation of unactivated alkenes. Unlike other methods, a vast array of functional groups is tolerated at the nitrogen and alkene moieties. The reaction produces the corresponding nitrogen-containing compounds in excellent yields and good diastereoselectivities. The use of HFIP as solvent proved crucial for the proper carrying out of this trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
42
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 77 publications
(25 reference statements)
1
42
0
2
Order By: Relevance
“…[2a,18] In this way,selectivity will be achieved not only for the protonation of the alkyne and the addition of TFSI in the presence of other, more electron rich, nucleophiles (H 2 O, arene,p roduct), but also for the lessfavored Natom within TFSI. [19] As Li + ions strive for ac oordination number of 4-6 in non-aqueous solution, [20] it is typically further coordinated to additional TFSI anions,s olvent molecules,o rw ater. [12c] In acomplex with Li + ,insolution, the TFSI anion adopts a cis conformation and is bound to aL i + ion in a h 2 -O,O' mode.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[2a,18] In this way,selectivity will be achieved not only for the protonation of the alkyne and the addition of TFSI in the presence of other, more electron rich, nucleophiles (H 2 O, arene,p roduct), but also for the lessfavored Natom within TFSI. [19] As Li + ions strive for ac oordination number of 4-6 in non-aqueous solution, [20] it is typically further coordinated to additional TFSI anions,s olvent molecules,o rw ater. [12c] In acomplex with Li + ,insolution, the TFSI anion adopts a cis conformation and is bound to aL i + ion in a h 2 -O,O' mode.…”
mentioning
confidence: 99%
“…[12c] In acomplex with Li + ,insolution, the TFSI anion adopts a cis conformation and is bound to aL i + ion in a h 2 -O,O' mode. [19] As Li + ions strive for ac oordination number of 4-6 in non-aqueous solution, [20] it is typically further coordinated to additional TFSI anions,s olvent molecules,o rw ater. Water, especially in trace amounts,i s known to have as ignificant impact on the outcome of selfassembly processes [21] and to enhance the formation and stability of alkaline earth metal complexes.…”
mentioning
confidence: 99%
“…6m,6q Visible-light photoredox protocols are curbed with similar limitations (Schemes 1g-1h). 12 Our recent studies demonstrated that the use of HFIP as a solvent 13 paired with a Lewis or Brønsted acid enables the activation of highly unreactive olefins. 8f,14 Conceptually, the role of the catalyst in these examples is not to directly activate the nucleophile or the electrophile, but, instead, to augment the acidity of a H-bond network of HFIP molecules.…”
Section: Nhac Critical For the Reaction (No Reaction With Nmeac)mentioning
confidence: 99%
“…[10] In der Tath at sein nicht-nukleophiler Charakter es als Gegenanion beliebt gemacht. [12c] In einem Komplex mit Li + in Lçsung nimmt das TFSI-Anion eine cis-Konformation ein und ist in einem h 2 -O,O'-Modus [19] an Li + gebunden. Diese Arbeiten beweisen zudem, dass die Regioselektivitäte ine dritte Herausforderung darstellt.…”
unclassified
“…Als Te mplat wurde Lithium gewählt, aufgrund der einfachen Verfügbarkeit von LiNTf 2 ,u nd wegen der besonderen Bedeutung von Lithium bei einer N-selektiven Addition von TFSI. [12c] In einem Komplex mit Li + in Lçsung nimmt das TFSI-Anion eine cis-Konformation ein und ist in einem h 2 -O,O'-Modus [19] an Li + gebunden. Da Li + -Ionen eine Koordinationszahl von 4-6 in nicht-wässriger Lçsung anstreben, [20] werden sie in der Regel durch zusätzliche TFSI-Anionen, Lçsungsmittelmoleküle oder Wasser koordinativ gesättigt.…”
unclassified